"If those to whom the W/word of God came were called gods ..."– Logos, wisdom and prophecy, and John 10:22–30 - Draper, Jonathan A. (HTS teologiese studies, 2015)
Jesus’ quotation of Psalm 82:6, ‘I said, You are gods’, a riposte to the accusation that he had blasphemed by making himself equal to God, has attracted considerable attention. The latest suggestion by Jerome H. Neyrey rightly insists that any solution to the problem should take account of the internal logic of the Psalm and argues that it derives from or prefigures a rabbinic Midrash on the Psalm which refers it to the restoration of the immortality lost by Adam to Israel at the giving of the Torah on Sinai. This immortality was then lost again because of the sin of the golden calf. Whilst agreeing that the Psalm is interpreted in the context of the giving of the Torah on Sinai, this article argues that its reference is directed towards Moses on Sinai rather than Israel in general. This accords with the interpretation of Philo and Josephus and other sources much earlier than the Mekkilta de Rabbi Ishmael that Moses is rightly called a god and is assumed to heaven in glory without dying. Rather than deny this attribution of divine features to Moses due to his reception of the Torah on Sinai, John argues that the Torah was received from the hands of Jesus as the Logos. Therefore, Moses’s derivative divine features simply confirm the true divinity of the Logos as the expression of the Father. Moses could be called a god because he knew Jesus as Logos and wrote about him (5:45–5:47), but he sinned and died like any mortal. The corollary is that Moses and his disciples lost their status and died like any mortal, whilst the disciples of Jesus who are ‘taught by God’ and believe in the Incarnate Logos (6:45), have not only seen the glory denied to Moses but are born from above to become divinised as tekna theou (1:12) and do not die.